Return to University Classrooms With Blended Learning: A Possible Post-pandemic COVID-19 Scenario - Cobo-Rendón, Rubia; Bruna Jofre, Carola; Lobos, Karla; Cisternas San Martin, Nataly; Guzman, Esteban (Frontiers in Education, 2022)
After more two years of the pandemic caused by COVID-19, a gradual return to face-to-face teaching has been taking place. Therefore, authorities need to put in place procedures to facilitate and ensure the quality of teaching during this process. The purpose of this article is to describe the strengths and challenges of implementing Blended Learning. The design used is consistent with a secondary investigation of a narrative review. As a result, several recommendations are presented for building institutional frameworks that enable the implementation of high-quality BL models in the context of a gradual return to face-to-face courses in higher education. From a theoretical and contextual perspective, considerations for transitioning to this model are discussed, based on lessons learned from emergency remote education. We conclude that the present post-pandemic scenario constitutes a pivotal moment for determining the way education is delivered in higher education.